2021
DOI: 10.3389/fphys.2021.701203
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Peptides and Cross-Talk With Other Factors in the Regulation of Insect Metabolism

Abstract: The insulin-like peptide (ILP) and insulin-like growth factor (IGF) signalling pathways play a crucial role in the regulation of metabolism, growth and development, fecundity, stress resistance, and lifespan. ILPs are encoded by multigene families that are expressed in nervous and non-nervous organs, including the midgut, salivary glands, and fat body, in a tissue- and stage-specific manner. Thus, more multidirectional and more complex control of insect metabolism can occur. ILPs are not the only factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 182 publications
0
54
1
Order By: Relevance
“…Furthermore, the presence of sugars or carbohydrates in the fat body stimulates the release of CCHamide-2 (CCHa2) and Unpaired 2 (Upd2) that each modify IIS in the brain ( Rajan and Perrimon, 2012 ; Li et al, 2013 ; Ren et al, 2015 ). There are numerous non-redundant mechanisms by which insulin is regulated before its secretion, and there are likely even more that extend beyond what we currently understand ( Teleman, 2009 ; Post and Tatar, 2016 ; Ahmad et al, 2020 ; Manière et al, 2020 ; Chowański et al, 2021 ; Ling and Raikhel, 2021 ). Non-nutritional cues and endogenous insulin decoys can modify IIS after secretion to generate more specialized physiological and behavioral responses ( Sloth Andersen et al, 2000 ; Siddle, 2012 ; Stefanatos et al, 2012 ; Okamoto et al, 2013 ; Barber et al, 2016 ).…”
Section: Insulinmentioning
confidence: 99%
“…Furthermore, the presence of sugars or carbohydrates in the fat body stimulates the release of CCHamide-2 (CCHa2) and Unpaired 2 (Upd2) that each modify IIS in the brain ( Rajan and Perrimon, 2012 ; Li et al, 2013 ; Ren et al, 2015 ). There are numerous non-redundant mechanisms by which insulin is regulated before its secretion, and there are likely even more that extend beyond what we currently understand ( Teleman, 2009 ; Post and Tatar, 2016 ; Ahmad et al, 2020 ; Manière et al, 2020 ; Chowański et al, 2021 ; Ling and Raikhel, 2021 ). Non-nutritional cues and endogenous insulin decoys can modify IIS after secretion to generate more specialized physiological and behavioral responses ( Sloth Andersen et al, 2000 ; Siddle, 2012 ; Stefanatos et al, 2012 ; Okamoto et al, 2013 ; Barber et al, 2016 ).…”
Section: Insulinmentioning
confidence: 99%
“…The interplay between SKs and ILPs have been studied also in D. melanogaster where it was shown that SK and ILPs were expressed in fly insulin producing cells (IPCs) indicating that they are likely to cooperate in regulation of feeding and metabolism (Chowański et al 2021 ; Söderberg et al 2012 ). It was shown that knockdown of either neuropeptide affects the transcript levels of the other, suggesting a possible feedback regulation between the SKs and ILPs (Söderberg et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, they can be classified into at least three subfamilies: insulin-like peptides, IGF-like peptides, and Dromo-ILP7-like peptides [ 29 ]. The similarities between human and insect ILPs concern a few aspects, the structural homology of hormones and their receptors, the mode of action (including signaling pathways), presence of additional agents of ILPs signaling (e.g., insulin receptor substrate (IRS)), and the physiological role of ILPs ( Table 1 ) [ 26 , 30 , 31 , 32 ]. In mammals, insulin is produced by β-cells of pancreatic islets, and in insects ILPs are mainly produced by brain insulin-like peptides and by cells in lateral organs like body fat or the gut [ 30 ].…”
Section: Peptides–neuropeptides–hormonesmentioning
confidence: 99%
“…The similarities between human and insect ILPs concern a few aspects, the structural homology of hormones and their receptors, the mode of action (including signaling pathways), presence of additional agents of ILPs signaling (e.g., insulin receptor substrate (IRS)), and the physiological role of ILPs ( Table 1 ) [ 26 , 30 , 31 , 32 ]. In mammals, insulin is produced by β-cells of pancreatic islets, and in insects ILPs are mainly produced by brain insulin-like peptides and by cells in lateral organs like body fat or the gut [ 30 ]. Nevertheless, it is suggested that IPCs in vertebrates and invertebrates may be derived from a common ancestry, despite the great differences in their anatomical localization, because of similar developmental programs involved in their specification [ 33 ].…”
Section: Peptides–neuropeptides–hormonesmentioning
confidence: 99%